Prospective randomized trial comparing radiofrequency ablation and complete saphenous vein stripping in patients with mild to moderate chronic venous disease with a 3-year follow-up - Sincos, Igor Rafael (2019)
Objective: To compare the use of the radiofrequency thermoablation of the saphenous vein with the ligation technique, and complete removal of the saphenous vein, from the saphenofemoral junction to the ankle. Methods: A total of 49 patients with chronic venous disease in the Comprehensive Classification System for Chronic Venous Disorders (CEAP) classes 2 to 4 for clinical signs, etiology, anatomic distribution and pathophysiology, were assessed at baseline, after 4 weeks, and after 1 year. The parameters assessed were complications, period of absence from activities, Venous Clinical Severity Score (VCSS) and quality of life scores according to Aberdeen Varicose Veins Questionnaire (AVVQ). They were re-examined 1 and 3 years after treatment to evaluate recurrence rates. Results: The success rate per limb (p=0.540), VCSS (p=0.636), AVVQ (p=0.163), and clinical complications were similar in the two treatment groups. Nevertheless, the radiofrequency thermoablation group had significant shorter length of hospital stay (0.69±0.47) and absence from activities (8.62±4.53), p<000.1. Conclusion: Patients submitted to radiofrequency thermoablation had an occlusion rate, clinical recurrence and improvement in quality of life comparable to removal of the saphenous vein. However, these patients spent less time hospitalized and away from their daily activities during recovering.